Understanding corruption through freehand drawings: a case study of undergraduate business students' visual learning in the classroom. Issue 1 (3rd April 2019) - Gadelshina, Gyuzel; Cornwell, Arrian; Spoors, David
Abstract: Interest in the role of visual literacy within education has grown significantly over the last 50 years. Many scholars maintain that living in an image-rich culture in the twenty-first century requires preparing visually literate graduates who are capable of a critical reading and understanding of visual texts, as well as constructing images through critical thinking. However, nowadays, discussion about visual learning and development of visual literacy competencies of students studying business and management remains quite limited. This paper presents a case study of a visual learning activity introduced to 1st year undergraduate students which are often referred to as 'digital natives'. This activity aims to develop students' visual critical thinking about a complex social phenomenon of corruption through their engagement with a non-digital activity such as freehand drawing.